Information and Communication Technology-Facilitated Sexual Violence (ICTFSV) pada Remaja: Pengalaman di Indonesia - Ismi Dwi Astuti Nurhaeni; Yusuf Kurniawan; Rino Ardhian Nugroho; Intan Insani Putri (Society, 2022)
This study discusses adolescents’ perceptions of ICT-facilitated sexual violence (ICTFSV) based on gender and school type. The research was conducted by surveying 719 students in seven regencies/cities in Surakarta, Indonesia, which were purposively selected. The ICTFSV indicator was measured based on the theories of Henry & Powell (2016) and Baumgartner et al. (2010). Mann-Whitney U and two-sided tests were employed to analyze the data. This study finds the different perceptions of ICTFSV based on gender at SHS and VHS. Moreover, it also finds the different perceptions of ICTFSV among students of SHS and VHS. This provides a new understanding of gender-perspective integration and character-building in developing school policies. Therefore, further research on gender equality and character-building of education policy can be carried out. The analyzed object imposes many limitations, namely the selected sample, the research focus, the data collecting, and analyzing method.